Decreased CSTA expression promotes lymphatic metastasis and predicts poor survival in oral squamous cell carcinoma. (June 2021) - Wang, Yupu; Wang, Lin; Li, Xing; Qu, Xingzhou; Han, Nannan; Ruan, Min; Zhang, Chenping
Highlights: Eight lymphatic metastasis-related hub genes were identified in OSCC. CSTA expression significantly correlated with tumor grade, nodal metastasis, and OS. Gain of cystatin A ( CSTA ) could suppress OSCC cell migration and invasion in vitro . Potential mechanisms for OSCC lymphatic metastasis were analyzed and discussed. Abstract: Objective: Herein, we aimed to identify biomarkers that affect lymphatic metastasis of oral squamous cell carcinoma (OSCC) through bioinformatic analysis, and clinicopathological and in vitro verifications. Design: The OSCC-related gene expression dataset was retrieved from The Cancer Genome Atlas (TCGA) and analyzed to identify differentially expressed genes (DEGs), which were subjected to pathway analysis. Weighted gene co-expression network analysis (WGCNA) and protein-protein interaction (PPI) network analysis were performed to identify hub genes. Expression of potential biomarkers was examined using quantitative real-time polymerase chain reaction, immunohistochemistry, and western blotting. Statistical analyses were performed to determine the association between biomarker expression and clinicopathological characteristics of patients with OSCC. Effects of selected biomarkers on proliferation, migration, and invasion were evaluated using in vitro assays. Results: For DEGs, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed potential lymphatic metastasis-related biological processes and signaling pathways. Eight hub genes — ALOXE3, CSTA, PLA2G4E, PPL, SPRR1A, SPRR2A, SPRR2D, and SPRR2E, were identified via WGCNA and PPI analyses. CSTA expression was markedly downregulated in primary OSCC tissues, and low CSTA expression significantly correlated with high tumor grade ( P  =  0.001), nodal metastasis ( P  =  0.028), and poor overall survival ( P  <  0.001). CTSA overexpression inhibited OSCC cell migration and invasion in vitro, with little effect on OSCC cell proliferation. Conclusions: Our study revealed that CSTA is a promising biomarker and therapeutic target with prognostic implications in patients with OSCC. CSTA may play an essential role in OSCC lymphatic metastasis and tumor differentiation.